Risiko Pajanan Logam Berat Pada Air Sungai - Muhammad Pahruddin (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Exposure risk of heavy metals on river water. River water is still used by the society as the primary source of drinking water although some rivers have been polluted by industry activities. The purpose of this research is to assess exposure risk of heavy metals which is contained in river water. In achieving the purpose, it conducted the measurement of insitu parameter as temperature, DO, turbidity and pH, mercury rate, manganese, cadmium, and chromium of 6 valence in 2 sample collecting points in Tabatan river, in headwaters and downstream of Desa Buas Buas and Sawaja Kecamatan Candi Laras Utara Kabupaten Tapin. The result of measurement is analyzed to predict exposure risk of heavy metals in river water consumed by people around the river. Exposure risk counts the intake (I). Hazard Index concluded that the control is necessary toward the exposure risk. The result of the research showed that only Manganese (Mn) is detected and exceed the limit. The value of I in age group of 1-